Autonomous guidance for intelligent missiles based on chaotic perception—action dynamics - Yu, X-L; Sun, Y; Liu, J; Xiang, W (Proceedings of the Institution of Mechanical Engineers. Part G, Journal of aerospace engineering, 2009)
Abstract In this article a new reactive mechanism based on perception—action dynamics for multi-sensory integration applied to an intelligent missile guidance system is proposed. The strategy is inspired by the olfactory bulb neural activity observed in rabbits subject to external stimuli. The new missile guidance technique exploits the use of a multiscroll chaotic system which is able to be controlled in real-time towards less complex orbits, such as periodic orbits or equilibrium points, considered as perceptive orbits. These are subject to real-time modifications on the basis of environmental changes acquired through a synthetic aperture radar sensory system. The mathematical details of the approach are given including simulation results in a virtual environment. The results demonstrate the capability of autonomous guidance for missile in complex spatial environments.